Analysis of the Strategy of the Development of the Old City Administration with the Concept Of Marketing Strategy: A Case Study in the Local Trade Area of Bandung City, West Java - Kaniawati, Keni; Nurani, Nina; Yenny; Alfiana, Maya (International Journal of Psychosocial Rehabilitation, 2020)
Structurally, cities can be seen as an area that administratively has boundaries and in which there are components of the population, economic systems, social systems, facilities, and infrastructure. Functionally, the city is the center of activity (economic and socio-cultural) as well as the center of settlements and functions as a center for the physical development of the area. This study examines the strategy of developing Old Town/Cultural Heritage (Chinatown) in the integrity of developing the potential of the region by developing the potential of non-Kota Tua areas/Cultural Heritage areas in order to have a significant economic value (sustainable development). not yet to highlight the potential of the region optimally. This is because many investors are less interested in developing the region due to the regulation of cultural heritage. Besides that, the financial capacity of the Bandung City government is limited to financing cultural heritage areas, while the ability of the community as owners is very limited, so all parties need participation in the preservation of cultural heritage buildings (the Chinatown area). In this study, the SWOT method was used with the IFAS-EFAS model, and the results showed stability, so that synergy was needed with the concept of the overall sustainable development.